Product strategies for export ventures : an empirical investigation among SMEs in an emerging economy - Abu H Ayob; Dana, Léo-Paul (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examines product strategies of firms in developing countries for export ventures in global markets. It focuses on generic product features: low cost, differentiation, and specialization for analysing how they are associated with the intent to export. A rigorous database was developed from a survey of 142 SMEs in Malaysia. Data was analysed through hierarchical ordinary least squares (OLS) regression analysis. This study finds that only products with differentiation, specialization, or both are intended for export. On the other hand, a low cost attribute deprives the intention of going global. In the context of this emerging economy, the optimal product strategy for exporting is differentiation and specialization coupled with low-cost strategy. The findings challenge traditional view that firms from developing countries possess cost advantage at the international level, thus justifying why some local firms remain reluctant to export.